2019
DOI: 10.2147/cmar.s233872
|View full text |Cite
|
Sign up to set email alerts
|

<p>Controlling Nutritional Status (CONUT) Score Is A Predictor Of Post-Operative Outcomes In Elderly Gastric Cancer Patients Undergoing Curative Gastrectomy: A Prospective Study</p>

Abstract: PurposeThe Controlling Nutritional Status (CONUT) score is a recently developed measure that is calculated using the serum albumin level, total cholesterol level, and lymphocyte counts. The aim of this study was to examine whether the CONUT score can predict post-operative outcomes in elderly patients undergoing curative gastrectomy.Patients and methodsPre-operative CONUT scores were evaluated from August 2014 to September 2016 in 357 gastric cancer patients who were scheduled to undergo curative gastrectomy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
4
9
0
Order By: Relevance
“…In addition, we identified age and RBC count as independent risk factors for complications. In other words, old age, anaemia and malnutrition had an adverse effect on short-term outcomes in patients after gastrectomy for GC, which was consistent with prior studies [ 39 , 40 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, we identified age and RBC count as independent risk factors for complications. In other words, old age, anaemia and malnutrition had an adverse effect on short-term outcomes in patients after gastrectomy for GC, which was consistent with prior studies [ 39 , 40 ].…”
Section: Discussionsupporting
confidence: 91%
“…For example, Ryo et al [ 17 ] determined the cut-off value of CONUT score as 2 for predicting mortality in 2 years and overall survival. Although the optimal value was different, the CONUT score still showed a good correlation with the outcomes of GC patients [ 17 , 39 ]. In addition, we identified age and RBC count as independent risk factors for complications.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we identi ed age and RBC count as independent risk factors for complications. In other words, old age, anaemia and malnutrition had an adverse effect on short-term outcomes in patients after gastrectomy for GC, which was consistent with prior studies 39,40 .…”
Section: Discussionsupporting
confidence: 90%
“…Ryo et al 17 mentioned the incidence of some complications, such as anastmostic leakage and intra-abdominal abscess, as related to the CONUT score. Huang et al 39 reported that the CONUT score was a signi cant risk factor for total complications and one-year survival in elderly GC patients. In our study, strati ed analysis of postoperative complications was further performed to compare low and high CONUT scores.…”
Section: Discussionmentioning
confidence: 99%
“…In addition we also identi ed age(P=0.037 OR=2.237 95%CI 1.048-4.774) preoperative RBC(P=0.003 OR=0.356 95%CI 0.180-0.707) as independent risk factors for complications. Generally speaking elderly patients anemia and malnutrition played adverse roles in short-term prognosis with patients after radical gastrectomy for cancer which was parallel to prior studies 38,39 . By the way we excluded albumin total lymphocyte count and cholesterol from multivariate analysis so as to avoid duplication.…”
Section: Discussionsupporting
confidence: 60%